Visual Semiotics Analysis on Webtoon Sweet Home - Nasution, Puja Indriana; Rangkuti, Rahmadsyah; Yusuf, Muhammad (Politeknik Harapan Bangsa Surakarta, 2021)
Webtoon is one of the mediums in delivering thoughts, point of view and life values with others; one of them is sweet home webtoon. By using visual Semiotic analysis, this study aimed to identify signs used in the Webtoon Sweet Home and to interpret the meanings of the Semiotic signs used in the Webtoon. The data source of this study is the serial comic entitled Sweet Home in the Webtoon which were technically collected using the qualitative method and visual materials in addition to applying the LINE Webtoon. Twenty six data were analyzed using the Visual Semiotic study proposed by Charles Sanders Peirce, including representamen, object and interpretant. Additionally, this study used three steps in interpreting the signs namely, non-verbal communicative legisign, framing techniques and communicative act. The study found that legisign was used on the panels in the Webtoon Sweet Home has general information in which the writer wishes to tell the readers. The legisign represents the meaning of the images portrayed in the Webtoon. Furthermore, the non-verbal communication legisign was identified based on facial expression, body language, posture and gesture. The framing technique concern what image shows, and the communicative act was analyzed based on the verbal sign found the Webtoon Sweet Home.